Human‐mediated dispersal of weed species during the Holocene: A case study of Chenopodium album agg. (18th March 2019) - Krak, Karol; Habibi, Farzaneh; Douda, Jan; Vít, Petr; Lomonosova, Maria N.; Wang, Lei; Mandák, Bohumil
Abstract: Aim: We hypothesised that during the Holocene, the distributions of species such as crop weeds have been significantly influenced by human activity. We aimed to (a) identify the main centres of diversity of the Chenopodium album agg. species and (b) test if these species colonised Europe from western Asia, most likely due to the westward expansion of agriculture in the Neolithic period. Location: Eurasia. Taxon: Chenopodium album aggregate (Amaranthaceae). Methods: Three cpDNA regions were sequenced in 904 individuals, from 26 species of the C. album aggregate. A dated phylogeny was inferred and this was used to establish relationships among the haplotypes and to estimate their divergence times. The group's main centres of diversity were inferred by comparing species and haplotype richness between Europe, the Mediterranean, western Asia, central Asia and Siberia. Results: The most haplotype‐diverse area for the entire C. album aggregate is central Asia. Interestingly, Europe is poor in terms of haplotype diversity, showing the same level of diversity as the western Asian region. The pairwise genetic differentiation between Europe, the Mediterranean and western Asia is lower than between any of these regions and either central Asia or Siberia. This points to the origin of the European Chenopodium species pool as being in western Asia. In some phylogenetically‐defined clades, species could not be distinguished based on cpDNA haplotypes due to a high level of haplotype sharing. However, in others, the haplotype variation follows the species boundaries. Main conclusions: Using the C. album agg. species as a model, we show the importance of central Asia as one of the main centres of diversity for weedy species. However, the group's colonisation of Europe had its origins in western Asia, highlighting the importance of human‐mediated dispersal of ruderal and weed plant species accompanying the westward spread of agriculture in the Neolithic period.